ANALISIS YURIDIS TERHADAP PERTIMBANGAN HAKIM PADA PERKARA HARTA BERSAMA AKIBAT PERCERAIAN DITINJAU DARI KOMPILASI HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN (PERKARA NOMOR 1726/PDT.G/2020/PA.BKS.) - Alivia, Siti; Amin Ash Shabah, Musyaffa; Supriyanto, Agus; Suprihatin, Suprihatin (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
The phenomenon of joint property disputes resulting from divorce occurred in the decision of the Bekasi Religious Court judge in case number 1726/Pdt.G/2020/PA.Bks, in this decision the panel of judges divided joint property outside the provisions stipulated by Article 97 of the Compilation of Islamic Law, where in the decision The division is 1/3 for the Plaintiff (ex-husband) and 2/3 for the Defendant (ex-wife). So this research aims to find out the legal basis for the judge's council's considerations in deciding cases and find out the relevance of decision number 1726/Pdt.G/2020/PA.Bks to the Compilation of Islamic Law and the Marriage Law. This research uses a qualitative research method, namely a descriptive analysis research method with a normative juridical research approach at the level of a statutory approach and a judge's decision approach. And decision number 1726/Pdt.G/2020/PA.Bks as the primary data source used in this research. The results of this research show that the panel of judges decided on the division of joint assets in the amount of 1/3 for the Plaintiff and 2/3 for the Defendant. The division was carried out by the panel of judges based on considerations and several pieces of evidence which showed that the Defendant (ex-wife) contributed more to the collection of joint assets from the results of his work, while the Plaintiff (ex-husband) admitted that his income was indeed small. The panel of judges did not use article 97 of the Compilation of Islamic Law in its decision which states that the distribution of joint assets is ½ for each party, the ex-husband and ex-wife. In this case the judge deemed it fair to determine the division of joint assets with 1/3 share for the Plaintiff (ex-husband) and 2/3 share for the Defendant (ex-wife). This judge's decision is in accordance with Satjipto Raharjo's progressive legal theory.